IMPLIKASI PERUBAHAN SOSIAL TERHADAP PERILAKU PERNIKAHAN SEJENIS DI MEDIA SOSIAL - Rahma, Fataqia; Salma (LPPM STAI Muhammadiyah Probolinggo, 2025)
Modern society is currently experiencing rapid transformation as a result of the influence of communication technology, especially social media. The use of social media has brought about significant changes in various aspects of human existence, including the realm of same-sex marriage. This study aims to find out about same-sex marriage, factors that influence same-sex marriage, and the influence of same-sex marriage on social media on the development of same-sex marriage in Indonesia. This research uses a qualitative methodology with a focus on descriptive techniques, specifically designed to gather insights about same-sex marriage on social media. The findings from this analysis reveal that Indonesia is one of the countries with a substantial social media user base, associated with widespread adoption of digital trends. The profound impact of social media work, changing various dimensions of society, this can give rise to various reactions from social media users. On the one hand, the reaction of rejection is negative comments and discrimination. While on the other hand, the reaction of supporters expresses their appreciation for same-sex marriage, celebrating the courage of those who speak out on social media. Keywords: Social Change, Same Sex Marriage, Social Media